Dual repair of traumatic flank hernia using laparoscopic and open approaches: a case report - Yoonjung Heo; Dong Hun Kim (Journal of Trauma and Injury)
Traumatic flank hernia (TFH) is rare and prone to recurrence, which makes appropriate treatment challenging. No current guidelines define the optimal timing and method of repair. Meanwhile, recent advances in laparoscopic techniques are reshaping the options for the treatment of TFH. A dual approach that utilizes both laparoscopic and open methods has not previously been reported. Herein, we present the successful treatment of TFH after blunt trauma. A 46-year-old male patient underwent elective herniorrhaphy on hospital day 3, in which laparoscopic implantation of a sublay mesh and extracorporeal implantation of an onlay mesh were performed. Such techniques may be appropriate and result in feasible outcomes in hemodynamically stable patients with large TFH who are strongly suspected of having bowel herniation or concomitant intraperitoneal injuries. Larger studies are needed to assess the long-term results.